Trophic ecology of introduced populations of Alaska blackfish (Dallia pectoralis) in the Cook Inlet Basin, Alaska - Eidam, Dona M. (Environ. Biol. Fishes, 2016)
Introduced non-native fishes have the potential to substantially alter aquatic ecology in the introduced range through competition and predation. The Alaska blackfish (Dallia pectoralis) is a freshwater fish endemic to Chukotka and Alaska north of the Alaska Range (Beringia); the species was introduced outside of its native range to the Cook Inlet Basin of Alaska in the 1950s, where it has since become widespread. Here we characterize the diet of Alaska blackfish at three Cook Inlet Basin sites, including a lake, a stream, and a wetland. We analyze stomach plus esophageal contents to assess potential impacts on native species via competition or predation. Alaska blackfish in the Cook Inlet Basin consume a wide range of prey, with major prey consisting of epiphytic/benthic dipteran larvae, gastropods, and ostracods. Diets of the introduced populations of Alaska blackfish are similar in composition to those of native juvenile salmonids and stickleback. Thus, Alaska blackfish may affect native fish populations via competition. Fish ranked third in prey importance for both lake and stream blackfish diets but were of minor importance for wetland blackfish.